Simultaneous size and density determination of polymeric colloids by continuous contrast variation in small angle X-ray scattering. (August 2016) - Garcia-Diez, Raul; Sikora, Aneta; Gollwitzer, Christian; Minelli, Caterina; Krumrey, Michael
Graphical abstract: Highlights: Many SAXS curves at different contrasts are easily measured with density gradient. Simultaneous size and density determination of polymeric colloids in the nanoscale. Results are validated through an inter-laboratory comparison. A novel approach to DCS is presented, by using two complementary centrifuge setups. The shape factor approach improves relevantly the accuracy of the size measurements. Abstract: Polymeric colloids are of growing importance in nanomedicine for drug or imaging agent delivery. Their characterization is a crucial task but their traceable size determination is challenging, especially for particles with a complicated inner structure. This work describes the simultaneous determination of the size distribution and the density of polymeric particles by means of continuous contrast variation in small angle X-ray scattering (SAXS), which also reveals the inner structure of the colloids. The applicability of the technique has been evaluated by the comparison with other techniques, with focus on differential centrifugal sedimentation (DCS) in terms of the measured density. A novel approach to DCS is presented, which employs two centrifuge setups to enable the density and size determination of particles with physical densities close to water.